(untitled) (Eurasian Journal of Philology Science and Education, 2015)
This scientific article is consider the fundamental trend of development of the cognitive and discourse linguistic, a principle the cognitive model of the discourse and text, be formed for a cognitive mape of the discourse. The novelty of the research is to describe the stages of modeling conceptual space of the text, which is based on identifying hierarchical relationships with the concept, the idea of genre and interactive models of discourse, as well as a framed text content, reflecting the concept of the study in the linguistic consciousness of native speakers. Cognitive map that integrates the text of his concept of serving the regulator and filter other concepts, frame-based situational or topically models and processes that relate to a single, global mental map (database) data model. The concept is the idea of totality macro position reflecting the essential nature of the semantic array of text. Disclosure laws verbalization of the concept is a testament to the existence of a single cognitive-semantic space of the text.